A Processor-Sharing Scheduling Strategy for NFV Nodes. (4th February 2016) - Faraci, Giuseppe; Lombardo, Alfio; Schembra, Giovanni
Abstract : The introduction of the two paradigms SDN and NFV to "softwarize" the current Internet is making management and resource allocation two key challenges in the evolution towards the Future Internet. In this context, this paper proposes Network-Aware Round Robin (NARR), a processor-sharing strategy, to reduce delays in traversing SDN/NFV nodes. The application of NARR alleviates the job of the Orchestrator by automatically working at the intranode level, dynamically assigning the processor slices to the virtual network functions (VNFs) according to the state of the queues associated with the output links of the network interface cards (NICs). An extensive simulation set is presented to show the improvements achieved with respect to two more processor-sharing strategies chosen as reference.